Efforts to overcome students’ learning difficulties in geometry: A didactic design of creative thinking skills through metacognitive approaches - Fauzi, KMS Muhammad Amin; Hia, Yasifati; Darari, Muhammad Bazlan; Siagian, Muhammad Daut (Beta: Jurnal Tadris Matematika, 2024)
[English]: Prior knowledge is crucial in connecting all available information so that new knowledge can be constructed through the processes of assimilation or accommodation. This study seeks to identify students’ prior knowledge related to their learning difficulties in solving mathematical problems on plane geometry and to describe a metacognition-based creative thinking learning trajectory that can help reduce these difficulties. The research method used is the didactic design research, comprising of three stages: the needs analysis, the metapedadidactic analysis, and the retrospective analysis. Quantitative and qualitative data are collected through test, questionnaire, observation, and interview. The findings show that, despite having prior knowledge, students still face difficulties in simplifying plane geometric shapes into smaller triangles or quadrilaterals, calculating their areas or perimeters, and understanding the relationships between various plane figures. To address these issues, a metacognition-based mathematical creative thinking learning trajectory was developed, consisting of five stages: problem orientation, planning to overcome the problem, implementing the plan, mastering initial mathematical knowledge (creativity concepts), and evaluating the results obtained. Based on the trial results, the developed didactic design series effectively reduces the difficulties faced by students. [Bahasa]: Pengetahuan awal merupakan hal yang paling krusial dalam menghubungkan seluruh informasi yang ada sehingga pengetahuan baru dapat dikonstruksi melalui proses asimilasi atau akomodasi. Penelitian ini bertujuan untuk mengidentifikasi pengetahuan awal mahasiswa kaitannya dengan kesulitan belajar dalam menyelesaikan masalah matematis pada materi bangun datar serta mendeskripsikan lintasan pembelajaran berpikir kreatif berbasis metakognisi yang dapat mengurangi kesulitan tersebut. Metode penelitian ini merupakan metode penelitian desain didaktik yang terdiri atas tiga tahapan, yaitu tahap analisis kebutuhan, tahap analisis metapedadidaktik, dan tahap analisis retrospektif. Data kuantitatif dan kualitatif dikumpulkan melalui tes, angket, observasi dan wawancara. Hasil penelitian menunjukkan bahwa, dengan pengetahuan awal yang ada, mahasiswa masih kesulitan dalam menyederhanakan bangun datar menjadi segitiga atau segi empat yang lebih kecil dan menghitung luas atau kelilingnya serta belum memahami hubungan antara berbagai bangun datar. Untuk mengantisipasi permasalahan tersebut, lintasan pembelajaran berpikir kreatif matematis berbasis metakognisi telah dikembangkan yang terdiri atas lima tahapan yaitu orientasi pada masalah, rencana mengatasi masalah, realisasi rencana, penguasaan pengetahuan matematika awal (konsep kreativitas), dan evaluasi hasil yang diperoleh. Berdasarkan hasil ujicoba, rangkaian desain didaktik yang dikembangkan dapat mengurangi kesulitan yang dihadapi mahasiswa.